Exploring the necessary conditions for observing interleaved practice benefits in math learning. (August 2022) - Mielicki, Marta K.; Wiley, Jennifer
Abstract: Previous research has demonstrated benefits of interleaved practice over blocked practice for learning mathematical formulas. This experiment tested whether the benefits from interleaved practice would generalize to more complex problems, where the problem type must be inferred from information in the problem. We compared delayed test performance of participants assigned to blocked practice to participants assigned to interleaved practice who had high or low practice performance. University students ( M age = 18.97, SD age = 1.50, 64% female) learned how to solve probability word problems in blocked practice, interleaved practice, or hybrid conditions that included both kinds of practice. Conditions that included some interleaved practice outperformed a condition that included only blocked practice at delayed test. Participants with high performance on interleaved practice problems outperformed participants assigned to blocked practice at delayed test. These results suggest that interleaved practice can confer learning advantages even for more complex problems. Highlights: Interleaving can lead to benefits in learning, even for complex problems. Interleaving benefits for complex problems may depend on competence after practice. Some interleaving during practice is more beneficial than no interleaving.